هۆكارەكانی قەیرانی دارایی و ئابوری لە هەرێمی كوردستان و ڕەنگدانەوەكانی لە نێوان ساڵانی 2014 – 2021 توێژینەوەیەكی تیۆری شیكارییە (توێژینەوەی هەڵێنجراو) - فرج, نجاە محمد; خدر, نوزاد علی (Sulaimani Journal for Humanities, 2022)
In this research, the financial and economic crisis in Kurdistan Region between (2014-2021) was mentioned, where the causes and repercussions of the crisis in various fields were clarified. The causes of this crisis have continued since 2014 until now, and it has many negative effects on social, health, economic and educational institutions. These data that were mentioned in the research show that the crisis prevents the growth of all different economic fields, as it is a source of exacerbation of social, educational and health and affects most public and private institutions and affects individuals and families in Kurdish community in Kurdistan region.